Narrativas de imigrantes haitianos em Cuiabá : formação escolar e profissional como perspectivas de inserção social - Freire, Paulo Paixão Alves (2017)
This study has the aim of knowing the professional and life history of Haitian immigrants in Cuiabá-MT and their perspectives of social insertion, starting from the School and Professional Education. Possible influences and permanence of racial stigmas and stereotypes about the Haitian immigrant in the current social imaginary were assumptions that initially supported the research, considering the ideas coming from the Racial Theories, of the Whitening Policies and Immigration, recurring in the XIX and XX centuries in Brazil. Therefore, we have prioritized the migratory flow of Haitians to Cuiabá-MT, from the event of the earthquake in Haiti in 2010. It was used the theoretical perspective of migratory networks, the qualitative approach and the investigative technique of oral history, supported in narratives, based on the script of semi-structured interviews. The research provided an opportunity to infer empirical data on the migratory flow of Haitians, especially after 2012, perceiving a racism that permeated the social and power configurations, recurrent in the moment of encounter between the Haitian immigrants with the local population, and how they see each other. At the same time, we have tried to verify, through the absence of official welcoming policies and insertion of these immigrants in the labor market, which point to a situation of social invisibility of this segment that brings with them silenced dreams and desires, as well as their own situation as immigrants, living in the capital of Mato Grosso State.